Nanbo3/pvdf composite: A flexible functional material - Teixeira, G. F. [UNESP]; Ciola, R. A. [UNESP]; Zaghete, M. A. [UNESP]; Varela, J. A. [UNESP]; Longo, E. [UNESP] (Wiley, 2017)
Sodium niobate can be used as precursor of flexible composites with great properties aiming the use in devices that combine properties like piezoelectricity and photoluminescence. In this work, we obtained NaNbO3 fiber-like particles and cubic-like particles by microwave-assisted hydrothermal method. The composites were made matching different volume fraction of NaNbO3 particles and PVDF polymer. The particles showed band gap around 3.3 eV and photoluminescence emission in blue region. The composites with less NaNbO3 volume fraction showed better flexibility. The piezoelectric property of composite with fiber particles was 7.8 pC/N and to composite with cubic particles the value was 1.1 pC/N. The UV-visible spectra of composites provided band gap values similar to particles. Photoluminescence emission of composites were in a lower energy region when compared to particles (590 nm to composite with fiber particles, and 550 nm to material with cubic-like particles), indicating contribution of different structural defects to emission. According the results, the anisotropy of NaNbO3 particles, improve the electrical and optical characteristics. Since the materials combine properties like piezoelectric and photoluminescence, they can have a potential application in flexible piezophotonic devices.